Energy availability in female collegiate beach volleyball athletes - Willingham, B. D.; Daou, M.; VanArsdale, J.; Thomas, M.; Saracino, P. G. (The Journal of Strength and Conditioning Research, 2024)
Low energy availability (LEA) is a present risk for many female athletes. Yet, the literature on LEA is often reliant on single, short-term, snapshots, which may not be reflective of the chronic energy balance surrounding female athletes in sport. Therefore, the purpose of this study was to establish the current prevalence of LEA in female collegiate beach volleyball athletes during the preseason and across the competitive season. One-way repeated measures analysis of variance was used to compare measures of EA (i.e., dietary intake, activity energy expenditure [EE], body composition) and EE (i.e., resting metabolic rate and thermic effect of feeding) at 4 timepoints—once in the preseason (i.e., Fall), and 3 times across the 10-week competitive season in Spring (i.e., week 1, week 5, and week 9). Significance was set at p = 0.05. Although mean EA was in the subclinical zone (i.e., 30-45 kcal·kg FFM-1·d-1) at each timepoint, the prevalence of LEA for individuals was 30.8% in the preseason, 37.5% at week 1, 25.0% at week 5, and 62.5% at week 9. Further, carbohydrate intake was below the recommended range for power athletes at each timepoint, suggesting that female beach volleyball athletes with LEA may benefit from increasing carbohydrate intake. Despite no statistical differences in body mass across the season (p = 0.577), there was a trend for increasing fat-free mass (p = 0.062) as the season progressed. Importantly, LEA is not a team-wide condition but an individual one. Therefore, approaches to mitigate LEA should be individualized.